Leadership of Caliph Abdurrahman Al-Nashir (929-961 AD) in Advancing Islamic Civilization in Andalusia - Ibnu Rusydi; Zakariyah Zakariyah (Indonesian Journal of Humanities and Social Sciences, 2023)
This article analyses Caliph Abdurrahman Al-Nashir's leadership (929-961 AD) in advancing Islamic civilization in Andalusia. Caliph Abdurrahman Al-Nasir is a successful Muslim leader who has run his government well. The method used in this research is historical research. This research concluded that the leadership of Caliph Abdurrahman Al-Nashir was a brave, strong, and visionary leader. Under Caliph Abdurrahman Al-Nashir's leadership, Andalusia enjoyed unprecedented peace and prosperity. This research shows that the history of the leadership of Caliph Abdurrahman Al-Nashir made peace and tolerance between Islam, Christians, and Jews intertwined and harmonious. Cordova became a city of knowledge because of the University of Cordova and became the center of knowledge in Europe. With all his achievements, it is unsurprising that the reign of Abdurrahman al-Nasir was the golden age of Islamic civilization in Spain.